Problematizing Argumentative Writing in an Iranian EFL Undergraduate Context - Ghanbari, Nasim; Salari, Mostafa (Frontiers in Psychology, 2022)
Argumentative writing is the most important genre that undergraduate students need to learn to meet their academic requirements. Hence, many studies in different ESL/EFL academic contexts have explored different aspects of argumentative essay at micro text level and also wider educational, contextual and cultural levels. However, majority of these studies have adopted a partial view and focused on individual aspects. Hence, in the absence of a comprehensive approach to undergraduate students’ argumentative writing in the EFL academic writing context, the present study was conducted by drawing on multiple data sources: students’ perceptions of the argumentative texts, writing teachers’ views on argumentative writing of the students and finally analysis of the structure of the argumentative texts written by the students. For this aim, a total of 100 argumentative essays written by the undergraduate students was analyzed. In addition, a group of 66 undergraduate students majoring in English literature and 20 university writing instructors were interviewed. The findings revealed that the concept of argumentation was poorly conceived and tackled with by the learners. Teachers also counted various grounds that students faced difficulties. Moreover, the structural analysis of the students’ texts showed that they had problems with developing secondary elements of argumentation. In sum, the study discusses that the failure to develop an argumentative essay by the Iranian undergraduate English majors entails several academic, contextual and pedagogical grounds. Implications for improving argumentative writing in the EAP context would be provided.